Persuasion and political ideologies in the discourse of Nelson Mandela - Faris, Ali Abdulhameed (2017)
It is worth mentioning that much discourse study has been conducted on the western discourse. Little research has been done on the discourse of non-western culture and non-western leaders.Against such backdrop, it could be said that discourse of nonwestern leaders has got more cultural and political significance because of its genuine role in shaping the life of millions of people in non-western communities. The rarity of research on non-western leaders has prompted the researcher to highlight the persuasive strategies and political ideologies in the discourse of the African leader Nelson Mandela whose discourse has influenced millions of people inside and outside South Africa. The universality of this African leader stems from his persuasive skills and influential ideologies. However, his biographical background has had its influence on shaping and determining his discourse. His culture and political position have definitely had their effect on his discourse. Specifically, this study aims to conduct a critical discourse analysis so as to investigate the various strategies and techniques of persuasion that are available to Nelson Mandela and to explore the embedded political ideologies, which shaped the notion of ingroupness and outgroupness in his discourse and contributed to determine, produce, and reproduce his discourse. For this purpose, three speeches were chosen selectively across two critical stages of his political life: before his imprisonment and after his imprisonment. The criteria for speeches collection is based on the critical and historical moments when speeches are likely to have a higher content of persuasive intent. To identify the persuasive strategies of Mandela, Johnstone’s (1989) 'Strategies for Persuasive Discourse' and Searle's (1979) 'Speech Act Theory' were utilized for the purpose of analysis. To uncover the embedded ideologies in Mandela's discourse, Van Dijk's (1998) 'Categories for Ideological Analysis' and Wodak's (2005) 'Discursive Strategies for Positive Self and Negative Other- Presentation' were advocated. The findings of the analysis showed that the utilization of Johnston's three persuasive strategies- quasilogical, presentational and analogical- was closely related to the context of the three speeches under investigation. Searle's speech acts-assertives, directives, commissives, expressives and declaratives- were consistently collaborated with Johnstone's persuasive strategies (quasilogical, presentational and analogical) so as to strengthen the social act of persuasion in the speeches under investigation. Mandela consistently employed various persuasive techniques and speech acts to provide audience not only with information on different socio-political or sociocultural issues but also to incite them to perform certain actions, namely sustaining unyielding struggle against the principles of apartheid which had brought forth segregation, poverty, and social inequality, and advocating interracial unity as it is the only access to democratized South Africa where all people regardless of their race or ethnicity would live without white or black domination. With the help of Van Dijk's strategies of actor description, positive self-presentation, and negative other-presentation, and Wodak's strategies of argumentation and perspectivation, the ideological themes of 'non-violence', 'violence' and 'interracial unity' were explored and discussed. The ideological analysis also manifested that Mandela's political ideologies were potential enough to create social identities- Black and White- through his employment of certain linguistic forms, for example, the pronoun "Us" which was used by him to emphasize group membership (self and others) and to reflect a sense of social and political exclusion or inclusion. The findings of the study manifested that Mandela's ideologies had the potential to influence the people of South Africa and the world. His ideologies were not restricted to merely the life of South Africans or the community of South Africa; they were an echo of universal issues, such as freedom, social equality, democracy, desegregation, and human dignity. Although his ideologies developed and changed across his political career, they remained revolving around one basic objective which was the freedom of the dominated in South Africa and the world and the democratization of South African community.